2015
DOI: 10.1016/j.vhri.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Costs of Hospital Stay in Specialized Diabetic Foot Department in Russia

Abstract: The cost for treatment of DFU by a multidisciplinary team in the federal medical institution was substantially higher than basic medical insurance tariff for this disease. Because revascularization procedures appeared to be the main cost driver, our results stress the need for careful implementation of this type of treatment for patients with DFU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…A study in Russia, concerning patients admitted to hospital due to a foot ulcer categorized by Wagner grade produced these average costs: grade 1e2450 V, grade 2e2821 V, grade 3e3937 V, and grade 4e5340 V. 56 Length of hospital stay, foot surgery, and vascular surgery had the greatest effect on cost.…”
Section: The Economic Burden To Health Care Systemmentioning
confidence: 98%
“…A study in Russia, concerning patients admitted to hospital due to a foot ulcer categorized by Wagner grade produced these average costs: grade 1e2450 V, grade 2e2821 V, grade 3e3937 V, and grade 4e5340 V. 56 Length of hospital stay, foot surgery, and vascular surgery had the greatest effect on cost.…”
Section: The Economic Burden To Health Care Systemmentioning
confidence: 98%
“…18 This is expected to reach 19% by 2045. 11 In Ghana, DFU prevalence was at 3.8 19 to 11%. 10 Singh et al reported that 11% to 14% of diabetic patients will develop foot ulcers, and about 6% to 23% of the foot ulcers may worsen and eventually lead to amputation.…”
Section: Introductionmentioning
confidence: 99%
“…3,7 Diabetic neuropathy often leads to the development of diabetic foot ulcers (DFUs), 8,9 where a thickened wound at the balls of the feet forms regardless of the duration. 10 Foot ulcer is the most common, but serious and costly complication of DM, [11][12][13] accounting for 7% to 11% of all hospital admissions in diabetic patients. 3,7,14 This affects societies and leaves a huge financial impact on low-income families and the health care system in developing nations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations